NOVEL PUTRI KUNANG-KUNANG KARYA TITI SETIYONINGSIH SEBAGAI MATERI AJAR BAHASA INDONESIA: KAJIAN STILISTIKA - Syihabuddin Mahmud Affandi; Kundharu Saddhono; Sri Hastuti (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This research aims to describe (1) the choice of words;  (2) language style; (3) imagery; and (4) its relevance towards Bahasa Indonesia learning process in high school regarding to “Putri Kuninang-Kunang” novel written by Titi Setiyoningsih. This study counts as qualitative reasearch using a novel entitled “Putri Kunang-Kunang” written by Titi Setiyoningsih, and the informants including teachers and students as the source of data. This research not only observed and recorded the choice of words, diction, and imagery  as the data but also combined the data with the informants statements to get the whole data. The technique took purpose sampling as the technique. The validity data was tested using triangulation method. The flowing analysis were chosen to analyse the whole data through the data reduction, the data presentation, and the conclusion. The result found that: (1) Dictions; there were 13 words related to personal characteristics, 2 grossier words, 12 loanwords, 6 nature reality words; (2) Language style or figurative language; there were 2 similes, 4 metaphores, 10 personifications, 2 pleonasms, 6 hyperboles, 1 satires, 2 paradox, 1 ironi, 2 sinism, 4 saracasms, 1 metonymy; (3) Imagery; there were 14 visual imagery, 8 auditory imagery, 4 olfactory imagery, 2 gustatory imagery, 17 movement imagery, and 4 touch imagery. The amount of the imagery had various numbers depends on its imagery. (4) The Novel entitled “Putri Kunang-Kunang” connected to Bahasa Indonesia learning process in High School as a teaching material of literary (novel) appreciation.